Do Red Seaweed Nanoparticles Enhance Bioremediation Capacity of Toxic Dyes from Aqueous Solution? - Abdallah Tageldein Mansour; Ahmed E. Alprol; Mohamed Ashour; Khaled M. A. Ramadan; Adnan H. M. Alhajji; Khamael M. Abualnaja (Gels, 2022)
Based on their functional groups, the use of various seaweed forms in phytoremediation has recently gained significant eco-friendly importance. The objective of this study was to determine whether a novel, sustainable, and ecologically acceptable adsorbent could be employed to remove toxic textile dye (Ismate Violet 2R (IV2R)) from an aqueous solution. The low-cost adsorbent was prepared from the nanoparticles form of the native red seaweed species, Pterocladia capillacea. Before and after the adsorption procedure, comprehensive characterization experiments on the bio-adsorbent were carried out, including BET, SEM, FTIR, UV, and dynamic light scattering (DLS) examination. The adsorption performance of the prepared nano-Pterocladia capillacea was optimized by adjusting operating parameters such as the initial dye concentration of 60 mg L−1, pH of 2, and contact time of 15 min, all of which were obtained by batch experiments in the lab. At the optimum conditions, the prepared adsorbent had maximum removal effectiveness of 87.2%. Most typical kinetics and isotherm models were used to test the experimental results. The equilibrium data fit well with the Langmuir isotherm model, with comparatively higher R2 values and fewer standard errors, while the pseudo-second-order kinetic model fits better with a decent correlation coefficient. Thermodynamic parameters revealed that the sorption process on nano-alga was exothermic and spontaneous.